1983
DOI: 10.1016/0304-3959(83)90203-8
|View full text |Cite
|
Sign up to set email alerts
|

Partial antagonism of placebo analgesia by naloxone

Abstract: Thirty subjects were given a placebo (intravenous saline), which was described as a known pain killer, once a week for 3 consecutive weeks. Experimental ischemic arm pain was produced prior to the placebo and again 1 h later. In a double blind procedure, half of the subjects received 10 mg of naloxone after placebo; the remaining subjects received naloxone vehicle. In addition to the placebo session, there were control and naloxone sessions each week to determine the normal changes in pain and the effect of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
1
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(111 citation statements)
references
References 10 publications
7
101
1
2
Order By: Relevance
“…The doses of ketamine and naloxone were chosen on the basis of the numerous previous studies using these drugs in various experimental and clinical pain models (e.g. Buchsbaum et al, 1977;Levine et al, 1979;Grevert et al, 1983;Guirimand et al, 2000;Brennum et al, 2001;Anderson et al, 2002, Bossard et al, 2002Strigo et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The doses of ketamine and naloxone were chosen on the basis of the numerous previous studies using these drugs in various experimental and clinical pain models (e.g. Buchsbaum et al, 1977;Levine et al, 1979;Grevert et al, 1983;Guirimand et al, 2000;Brennum et al, 2001;Anderson et al, 2002, Bossard et al, 2002Strigo et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…During both clinical and experimentally induced pain, placebo administration with expectation of analgesia has been associated with reductions in pain ratings that were reversed by either the open or hidden administration of naloxone (i.e., they were mediated by the activation of pain-suppressive endogenous opioid neurotransmission) (Gracely et al, 1983;Grevert et al, 1983;Levine and Gordon, 1984;Benedetti, 1996;Amanzio and Benedetti, 1999). Nonopioid mechanisms have also been described, particularly in the context of previous preconditioning with non-opioid agents (Amanzio and Benedetti, 1999).…”
Section: The Pharmacological Approachmentioning
confidence: 99%
“…Other studies indicate that endogenous opioids alone cannot account for placebo analgesia and the process may be configured through different mechanisms. For instance, experimental reports have shown that placebo analgesia may occur without the involvement of endogenous opioids or that under certain circumstance, naloxone only partially blocks the placebo analgesia effect (Gracely et al, 1983;Grevert et al, 1983;Amanzio and Benedetti, 1999).…”
Section: Introductionmentioning
confidence: 99%